Reactions of Secondary Phases with Carbon in Magnesia‐Carbon Bricks. Issue 11 (4th July 2016) - Redecker, Lisa; Sax, Almuth; Quirmbach, Peter; Jansen, Helge
Abstract : Despite the excellent thermochemical properties of magnesia carbon bricks, these exhibit one weak characteristic during their use: their carbothermally induced wear. Carbon has a high affinity to oxygen, which leads to a reaction between magnesia and carbon, forming gaseous products at very low oxygen partial pressures in the surrounding atmosphere. When magnesia carbon material is furthermore applied at negative pressures, the precited carbothermic reduction processes effect an internal decomposition or even degradation of the bricks. Mostly, high‐purity magnesia varieties (MgO ≥ 96 wt%) are used for the production of magnesia carbon bricks because the low‐melting calcium silicate secondary phases in magnesia impair the high‐temperature resistance of these bricks. The fundamental question if and to which extent secondary phases react with carbon and which impact they have on the carbothermally induced wear of bricks has been unsolved so far. The following paper presents which influence the mineral secondary phases, monticellite, merwinite, and belite that are most commonly occurring in magnesia, have on the carbothermally induced wear. The respective studies were conducted by means of thermogravimetric and microstructural analyses. The results of these studies show that monticellite in the MgO–C microstructure brings about an increase in weight loss on account of carbothermic reduction processes. On the contrary, belite and merwinite in the MgO–C structure do not exhibit any negative impact on the thermal stability of the microstructure.